Special Economic Zones in Russia: Results Evaluation and Development Prospects - Veronika Yu. Maslikhina (International Journal of Economics and Financial Issues, 2016)
The objective of the article is to analyze functioning efficiency of special economic zones (SEZs) in the Russian Federation and to assess their development prospects in the Russian regions. There are 36 SEZs of different types in 33 regions in Russia: industrial production, technology development, tourism and recreation, port and complex SEZs. The empirical basis of the research constitute legal acts of the Russia, the annual reports of authorities of the Russia on the SEZs functioning results. Methodical basis of the research constitute an official efficiency estimation technique of the Russian SEZs. The industrial production and technology development SEZs are the most effective. The potential of the tourism and recreation and port SEZs is not realized. Only industrial production SEZs can have a real impact on the regional economy. They can attract large companies and significant private investments, which will provide a large number of new jobs, high revenue and tax payments into the budget. Keywords: development institutions, special economic zone, regional development, Russia JEL Classifications: A10, R1, R58